Repurchase Decision on iPhone in Indonesia; The Influenced of Social Media between Utilitarian and Hedonic Values in Customer Satisfaction - Tommy Williams Handoyo, La Mani (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article examines consumer behavior influenced of social media on hedonic and utilitarian values in customer satisfaction, which has led to an iPhone repurchase decision in Indonesia. Purpose: To find out whether there is a significant influence of social media on the hedonic and utilitarian value on consumer satisfaction in using the iPhone by making iPhone repurchase decisions in Indonesia. Although previous research has identified some precursors to customer satisfaction, limited research has paid attention to the hedonic and utilitarian value in customer satisfaction. Research design, data, and methodology: the validity test, reliability test, and multiple linear regression test using the SPSS 20 application. The population studied is iPhone users in Indonesia. The research sample was 384 people. Results: The influence of social media on hedonic and utilitarian values in consumer satisfaction is using the iPhone so that in Indonesia, consumers decide to repurchase iPhones. This article concludes that consumers consider the hedonic and utilitarian value in their satisfaction resulting in their iPhone repurchase decision in Indonesia. Conclusions: The results are useful for the PT Apple Indonesia (Branch of Apple Inc. in Indonesia) to better understand the iPhone users' need for the product. Therefore, the iPhone users' would like to repurchase when Apple Inc. launched a new product of iPhone.